2012
DOI: 10.4028/www.scientific.net/msf.706-709.2418
|View full text |Cite
|
Sign up to set email alerts
|

Tensile Properties of Low Angle Boundaries of Single Crystal Superalloy DD6

Abstract: The tensile properties of DD6 alloy with twist low angle boundaries were investigated at 760°C, 850°C and 980°C, and the misorientation angle of twist low angle boundaries of the specimens of the alloy varies from 0º to 12º. The results showed that when the angle of low angle boundaries is relatively small, it has a little effect on the tensile properties of the alloy. It is notable that effects of low angle boundaries on the tensile strength are weaker than those on the tensile elongation. The characteristic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…And for the 10°grain boundary model, the addition of the μ phase could induce a significant drop of tensile stress. Previous research works showed a dramatic drop of tensile of grain boundaries stress when the misorientation increased to some extent [7][8][9][19][20][21][22][23]. According to our experiment and simulation, it can be proved that the serious deterioration of mechanical properties in the single crystal superalloy DD6 is caused by the precipitation of the μ phase at the grain boundaries when the misorientation angle exceeds about 10°.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…And for the 10°grain boundary model, the addition of the μ phase could induce a significant drop of tensile stress. Previous research works showed a dramatic drop of tensile of grain boundaries stress when the misorientation increased to some extent [7][8][9][19][20][21][22][23]. According to our experiment and simulation, it can be proved that the serious deterioration of mechanical properties in the single crystal superalloy DD6 is caused by the precipitation of the μ phase at the grain boundaries when the misorientation angle exceeds about 10°.…”
Section: Discussionmentioning
confidence: 56%
“…DD6 is a second generation single crystal superalloy containing about 2 wt% Re developed for areoengine blade applications [18], and numerous studies have been taken to study the mechanical properties of grain boundaries with different misorientation angles and showed that both the tensile and creep properties of DD6 single crystal superalloy were reduced by the formation of grain boundaries. The mechanical properties of DD6 single crystal superalloy gradually decrease with increasing misorientation angle when the misorientation angle is less than about 10°, while a significant deterioration of mechanical properties takes place when the misorientation exceeds about 10° [17,[19][20][21][22][23]. In this study, we aimed to study the misorientation related microstructure at grain boundary in DD6 single crystal superalloy and their relationship to mechanical properties of the single crystal superalloy.…”
Section: Introductionmentioning
confidence: 99%
“…It is worth mentioning that the material constants A oct , R oct , A cub , and R cub are related to the orientation factor f which is defined as: fgoodbreak=E001/Eitalichkl where [ hkl ] is Miller indices in material coordinate system, E [001] and E [ hkl ] are the elastic modulus at [001] orientation and [ hkl ] orientation 48,49 . The elastic modules and ultimate tensile strengths of nickel‐based single crystal superalloy DD6 in [001], [011], and [111] orientation are shown in Table 2 and Figure 1(A), respectively 47,50,51 . The specimen used in uniaxial tensile tests in Refs.…”
Section: Anisotropic Creep Lifetime Prediction Modelmentioning
confidence: 99%
“…The specimen used in uniaxial tensile tests in Refs. [47, 50, 51] is DD6 standard specimen with 5‐mm‐diameter test section. The creep lifetime predictions for DD6 standard specimens with different orientations are shown in Figure 1(B)‐(F), and most of the predicted creep lifetimes are within a scatter band of factor 2, which verifies the accuracy of the creep lifetime prediction model.…”
Section: Anisotropic Creep Lifetime Prediction Modelmentioning
confidence: 99%
See 1 more Smart Citation